2022
DOI: 10.46325/gabj.v6i1.201
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder Duck Farmers’ Breeding Practices and Trait Preferences in Nasarawa State, Nigeria

Abstract: Duck keeping is a very important sector in resource-constrained families as it provides for family proteins and income and other social needs. The present study was carried out to determine the influence of gender on livestock breeding practices of duck farmers in Nasarawa State, Nigeria. A total of 100 duck keepers (36 males and 64 females) were randomly sampled. Primary data were collected through individual structured questionnaire administration. Chi-square (χ2) statistics were used to compare categorical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…However,Ninvilai et al (2020) observed susceptibility across all ages, suggesting a need for further research into the speci c factors in uencing this initial vulnerability in our study.Duck mortality varied across agroecological zones, with Zone 8 (Adjohoun, Come, Dangbo, Grand Popo, Lokossa and Ouidah) having lower mortality throughout reproduction (0-3 weeks and 0-adulthood) compared to Zones 5(Aplahoue) and 6 (Abomey calavi, Allada,Dogbo, Misserete and Tori-Bossito) while Zone 5 had lower mortality during the rearing phase (3 weeks to adulthood). These variations suggest potential in uences of environmental factors or management practices speci c to each zone as describe by the study of(Yakubu and Moses, 2022). Further studies are required to pinpoint the speci c factors driving these zone-based variations in mortality.…”
mentioning
confidence: 99%
“…However,Ninvilai et al (2020) observed susceptibility across all ages, suggesting a need for further research into the speci c factors in uencing this initial vulnerability in our study.Duck mortality varied across agroecological zones, with Zone 8 (Adjohoun, Come, Dangbo, Grand Popo, Lokossa and Ouidah) having lower mortality throughout reproduction (0-3 weeks and 0-adulthood) compared to Zones 5(Aplahoue) and 6 (Abomey calavi, Allada,Dogbo, Misserete and Tori-Bossito) while Zone 5 had lower mortality during the rearing phase (3 weeks to adulthood). These variations suggest potential in uences of environmental factors or management practices speci c to each zone as describe by the study of(Yakubu and Moses, 2022). Further studies are required to pinpoint the speci c factors driving these zone-based variations in mortality.…”
mentioning
confidence: 99%